EKSTRAK DAUN MINDI (Melia azedarach) SEBAGAI BIOINSEKTISIDA UNTUK PENGENDALIAN INFEKSI Chrysomya bezziana PADADOMBA - Yulvian Sani (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Parasitic dermatitis may cause economic loss for livestock industry if it is not approriately controlled. Among the preventive measures available presently, the use of plant-derived insecticides is regarding as an alternative approach to control the disease since it is environmental and animal health safe. The purpose of this study was to assess the effects of mindi (Melia azedarach Linn.) extract leaves for controling Chrysomya bezziana in vitro and in vivo.The study showed that the methanolic extract of M.azedarach leaves affected various stages of C. bezziana larvae.A topical application of 0.25% methanol extract in vaseline mixture killed and inhibited the growth of larvae and reduced weight gain of both LI and LI larvae.The average mortality rate in a treated group (26%) was higher than a control group (19.2%).Greater reduction of average weight gain was also seen in the treated group (0.2719 gr.) compared to the control group (0.4761 gr). The larvae apparently had smaller size and wrinkled shape of anatomical structure seeming that they were inappropriately grown. While the average mortality rate of L2 was found higher in the treated group (46.8%) than the control group (22.4%). The leaf-methanol extract had greater effect to L2 than LI as seen higher mortality rate in L2 (46.8%) than the LI (26%). In conclusion that the higher dose rate of methanol extract applied will lead to high mortality of the larvae. The low mortality rate may be due to low concentration (0.25%) of leaf extract applied and short period of time for bioassay.These findings seem very promising, suggesting that may possible to increase larvicidal effects by increasing the concentration and time of assessment.